Controllable water behaviors on V-shape micro-grooved titanium alloy surfaces depending on the depth-to-width aspect ratio. (September 2021) - Wang, H.; He, M.; Liu, H.; Guan, Y.
Abstract: Active manipulation of liquid spreading behaviors on solid surface is important due to various applications in artificial fluid-transport and liquid harvesting systems. Generally, super-spreading property can be achieved by constructing micro/nanoscale structures on hydrophilic surface on the basis of the structure induced capillary force, however it hardly proceeds on hydrophobic surface in controllable manner. Herein, based on the laser induced "double modification" of surface morphology and chemical composition, we fabricate V-shape microgrooves on hydrophobic solid surface with different depth-to-width (D/W) aspect ratios, on which liquid can be either super-spreading (SS) or non-spreading (NS) depending on the D/W ratio of microgrooves. Experimental results demonstrate that water droplet can hardly spread on the grooved surface when D/W ratio is lower than 0.6, while exhibit super-spreading property on the surface when D/W ratio is higher than 0.7. In the process of water spreading in SS microgrooves, water flow dynamics are found to satisfy z ( t ) ∼ t 1 / 2, z ( t ) ∼ t 1 / 2 + t and exponential functions successively when taking gravity effect into consideration. Active manipulation of water behaviors is achieved by combining SS and NS microgrooves, where water rapidly propagates along SS microgrooves and immediately stops when it reaches NS ones. This study provides a facile method for realizing active and spontaneous manipulation of water spreading behaviors on demand. Graphical abstract: Image 1 Highlights: V-shape microgrooves with different D/W ratio were produced via laser fabricating method to realize water SS or NS property. Active manipulation of water dynamic behavior was achieved on hydrophobic surface by constructing SS and NS microgrooves. Taking gravity into account, water dynamics on SS surface follow, and exponential functions successively in flow process.